2016
DOI: 10.1016/j.actamat.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Spark-plasma-sintering and finite element method: From the identification of the sintering parameters of a submicronic α-alumina powder to the development of complex shapes

Abstract: Spark-plasma-sintering and finite element method: From the identification of the sintering parameters of a submicronic α-alumina powder to the development of complex shapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 16 publications
3
63
0
1
Order By: Relevance
“…The present SPS process consolidates powders in a short time and under a high pressure which impedes the grain growth and solute diffusion20. However, our previous work indicated that SPS of nitrided Ta particles only prepared a gradient N concentration without core-shell structure21.…”
Section: Resultsmentioning
confidence: 84%
“…The present SPS process consolidates powders in a short time and under a high pressure which impedes the grain growth and solute diffusion20. However, our previous work indicated that SPS of nitrided Ta particles only prepared a gradient N concentration without core-shell structure21.…”
Section: Resultsmentioning
confidence: 84%
“…The shrinkage curves introduced into the model (Fig. 3) are calculated by an analytic Olevsky's model for sintering [18] previously determined for our alumina powder [19]. The Table 1 Physical properties of inconel, graphite and alumina (with T in Kelvin).…”
Section: The Joule Heating Modelmentioning
confidence: 99%
“…The punch/die ECR is globally modelled here by a resistive layer with an anisotropic effective electrical resistivity e ( ex , ey ) of thickness 0.2 mm, corresponding to the initial punch/die gap where the papyex is introduced, which is assumed constant (19).…”
Section: Spacer/punch Punch/sample Sample/die and Punch/die Calibramentioning
confidence: 99%
“…We showed in a previous work [30] that this intrinsic difficulty is responsible for densification inhomogeneity for all die compaction type processes. In a complex shape, the areas of small thickness need lesser densification distance than the high thickness area.…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulty of the multiple parts configurations is the temperature homogeneity. Finite Element Method (FEM) simulations of the Joule heating [12][13][14][15][16][17][18][19][20][21][22] and the densification [23][24][25][26][27][28][29][30] are performed by many authors, with the aim of predicting the temperature and densification field and find optimized solutions [10,[31][32][33][34][35][36]. In previous work [11], we showed that a homogenization of the temperature field can be attained for multiple parts configurations by adjusting the electric current flow with electric insulations and specific geometrical tricks.…”
Section: Introductionmentioning
confidence: 99%